2020
DOI: 10.1101/2020.11.26.20239368
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Estimation and worldwide monitoring of the effective reproductive number of SARS-CoV-2

Abstract: The effective reproductive number Re is a key indicator of the growth of an epidemic. Since the SARS-CoV-2 pandemic started, many methods and online dashboards have sprung up to monitor this number. However, these methods are not always thoroughly tested or are applied only to a limited geographic range. Here, we present a method for near real time monitoring of Re, applied to epidemic data from 170 countries. We thoroughly validate the method on simulated data, and present an intuitive web interface for inter… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(79 citation statements)
references
References 69 publications
1
77
0
1
Order By: Relevance
“…This method was applied to AIDS cases, which feature long delays from infection to observation [ 48 ], and in the reconstruction of incidence from mortality times series for the 2009 H1N1 (swine flu) pandemic [ 46 ]. It is now being applied to COVID-19 [ 8 , 49 ]. Fig 5 shows an example of deconvolution applied following the methods in [ 46 ].…”
Section: Adjusting For Delaysmentioning
confidence: 99%
See 2 more Smart Citations
“…This method was applied to AIDS cases, which feature long delays from infection to observation [ 48 ], and in the reconstruction of incidence from mortality times series for the 2009 H1N1 (swine flu) pandemic [ 46 ]. It is now being applied to COVID-19 [ 8 , 49 ]. Fig 5 shows an example of deconvolution applied following the methods in [ 46 ].…”
Section: Adjusting For Delaysmentioning
confidence: 99%
“…The simplest approach is to drop estimates on the last few dates or to flag them as unreliable [ 8 ]. But many methods are available to adjust for right truncation, which can improve real-time analysis [ 42 , 54 , 59 ].…”
Section: Adjusting For Right Truncationmentioning
confidence: 99%
See 1 more Smart Citation
“…In many regions around the world, the effect of social distancing interventions is monitored in real-time using estimates of the time-dependent reproduction number R t (e.g. [ 22 ]). We applied standard procedures for calculating R t [ 23 ] to the incidence data from our simulations, and using the time at which R t first crossed the threshold of 1 as a measure of the delay, we found that the trends agreed with those reported for the epidemic peak ( S8 Fig ).…”
Section: Resultsmentioning
confidence: 99%
“…We obtained the data from the Report on Weekly Deaths from the South Africa Medical Research Council Burden of Disease Research Unit 40 . We generated estimates for the effective reproduction number (Re) of SARS-CoV-2 in South Africa from the covid-19-re data repository (https://github.com/covid-19-Re/ dailyRe-Data) as of 14 December 2020 41 .…”
Section: Epidemiological Dynamicsmentioning
confidence: 99%